Sistema estomatognático, postura e qualidade de vida de docentes na pandemia de Covid-19 - Vivian, Gustavo Jacobsen (2023)
Introduction: Body posture is the position of the body in which the spine stands erect against gravity, respecting physiological curves. Postural deviations are changes in the spine that cause curves in the region to become more pronounced. They contribute to the vertebral discs becoming compressed, which is caused by improper posture. These changes and injuries in the cranial or cervical region can generate changes in the stomatognathic system because of the muscular synergy of these regions. The most evident changes in the stomatognathic system are the loss of strength and the decrease in muscle tone that interfere with the performance of its functions, making evident the inter-relationships of oral health with mastication and swallowing, changes that directly influence the quality of life. The daily lives of workers and their work environments have changed thanks to the COVID-19 pandemic. Changes such as telecommuting have generated more emotional and physical stress, as a result of longer hours and time spent in front of screens. With this change many professionals, such as university professors, have had to adapt their classrooms to their own homes, and teach through online support. Thus, a possible loss in the health of this population may be associated with general quality of life conditions, including the stomatognathic system, body posture, and mental health. Purpose: To assess masticatory function, cervical and masticatory myoelectric activity, body posture, as well as quality of life in higher education teachers during the COVID-19 pandemic. Methods: A prospective, quantitative, cross-sectional and analytical field study was conducted at the Laboratory of Orofacial Motricity (LABMO) at the Federal University of Santa Maria (UFSM). After initial contact through digital invitations during the pandemic, the volunteers answered an online questionnaire with data on eligibility criteria and were later evaluated in person regarding clinical aspects of the stomatognathic system, body posture, electrical activity of the cervical and masticatory muscles, and quality of life. The independent variables were: gender, age group and physical activity. As dependent variables among others: masticatory pattern, normalized electrical activity of TPD, TPE, ECD ECE, MD, ME, TD and TE; cervical posture, head position and relative position of the high cervical spine, QL scores.The data were statistically analyzed considering a significance level of 5%, through the software Statistica 9.0. Results: The sample consisted of 21 higher education professors, six males and 15 females, ranging in age from 26 to 62 years (mean age 38.47 years). Among men, the mean age was 33.83 years, and among women, 40.27 years. As for the masticatory function, the findings were significant for females; it was possible to verify significance for the bilateral alternating masticatory pattern in teachers over 44 years old; myoelectric activity of the cervical musculature, it was observed significance according to the male sex; The myoelectric activity of the cervical musculature was significant for males; the horizontal alignment of the head was significant for females under 44 years of age; the vertical alignment of the head was significant for males and for teachers with a higher level of physical activity; the scores of quality of life were significant for functional capacity in females and social aspects in teachers under 44 years of age. Conclusion: The university professors obtained an impairment in their masticatory function, myoelectric capacity of the cervical and masticatory muscles, cervical posture, and quality of life during the COVID-19 pandemic period.